PENGARUH KEMUDAHAN DAN MANFAAT E-FAKTUR TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PEMAHAMAN INTERNET SEBAGAI VARIABEL MODERASI - Aqilah Khairunnisa; Andi Nurwanah; Hamzah Ahmad (Jurnal Riset Perpajakan: Amnesty, 2021)
This research was intended to know of ease of use of e – faktur and the usefulness of e – faktur to tax payers compliance with understanding the internet as a moderating variable in The South Makassar Primary Tax Office. The population in this study were taxpayers registered at KPP Pratama South Makassar, namely 83,501 taxpayers, while the sample of this study were 100 taxable entrepreneurs who registered using e-invoice at KPP  Pratama South Makassar. The data analysis technique used  descriptive statistical techniques and Multiple Linear Regression assisted  by SPSS 25.0. The results of the research showed that ease of use of e – faktur and the usefulness of e – faktur positively and significantly affect on the tax payers compliance. understanding the internet can not moderate the effect of ease of use of e – faktur and the usefulness of e – faktur on tax compliance.